The Handbook of fashion studies - Black, Sandy (Bloomsbury Academic, 2013)
"The Handbook of Fashion Studies identifies an innovative spectrum of thematic approaches, key strands and interdisciplinary concepts that continue to push forward the boundaries of fashion studies. The book is divided into seven sections: Fashion, Identity and Difference; Spaces of Fashion; Fashion and Materiality; Fashion, Agency and Policy; Science, Technology and New fashion; Fashion and Time and, Sustainable Fashion in a Globalised world.Each section consists of approximately four essays authored by established researchers in the field from the UK, USA, Netherlands, Sweden, Canada and Australia. The essays are written by international subject specialists who each engage with their section's theme in the light of their own discipline and provide clear case-studies to further knowledge on fashion. This consistency provides clarity and permits comparative analysis.The handbook will be essential reading for students of fashion as well as professionals in the industry"--Provided by publisher.